AB0839 RELIABILITY OF COMPOSITE MEASURES FOR THE ASSESSMENT OF PSORIATIC ARTHRITIS. (2nd June 2020) - Tillett, W.; Helliwell, P.; Fitzgerald, O.; Waxman, R.; Antony, A.; Coates, L. C.; Jadon, D.; Creamer, P.; Lane, S.; Massarotti, M.; Cavill, C.; Brooke, M.; et al.
Abstract : Background: Composite measures of disease activity have been developed for use in Psoriatic Arthritis (PsA) to capture the wide spectrum of disease but there is a lack of consensus regarding which to adopt for routine practice. It is recognised that more data is required to understand the measurement properties of existing instruments and consider the impact of modifications that may improve face validity, responsiveness or feasibility. It is important to have an estimate of a measurement instrument's reliability in the setting of stable disease in order to understand measurement error and responsiveness. To our knowledge no data exists on the stability of composite measures in PsA. Objectives: To measure test re-test reliability of composite measures of disease activity in PsA. Methods: Clinical and patient reported outcomes to enable the calculation of composite measures were administered to 141 patients with PsA at five time points in a UK multicentre observational study. All patients fulfilled the CASPAR criteria. Twenty-nine patients with clinically stable disease and receiving no treatment intervention underwent repeat assessment by the same examiner within 2 weeks. Patients in high and low disease were included. Reliability was evaluated by intra-class correlation coefficient (ICC) and Bland Altman plots. Results: Of the 29 patients included 15 were male, the mean age was 52.4 years (SD 13.39), mean disease duration at T0 was 9.2yrs (SD 8.11). The mean swollen joint count was 3.4 (SD 5.1), tender joint count 11.3 (SD 15.03) and PASI 1.0 (SD1.04). The ICC (95% CI) for tender and swollen joint counts were 0.94 (0.87-0.97) and 0.91 (0.80-0.96) respectively. The ICC for PASI was 0.95 (0.90-0.98). All composite measures demonstrated high levels of test-retest reliability with ICC >0.85, table. The most reliable measure was the PADAS ICC 0.98 (95% CI 0.954-0.991). The individual ICC for each composite measures are reported in the table and Bland Altman plots, figure. Conclusion: All composite measures show high levels of test-retest reliability in this cohort. The PASDAS was the most stable measure. Modifications to these instruments can now be tested and the impact compared to the original versions. Funding: This report is independent research funded by the National Institute for Health Research, Programme Grants for Applied Research [Early detection to improve outcome in patients with undiagnosed PsA ('PROMPT'), RP-PG-1212-20007]. The views expressed are those of the authors and not necessarily those of the NIHR or the Department of Health and Social Care. Disclosure of Interests: William Tillett Grant/research support from: AbbVie, Celgene, Eli Lilly, Janssen, Novartis, Pfizer Inc, UCB, Consultant of: AbbVie, Amgen, Celgene, Lilly, Janssen, Novartis, MSD, Pfizer Inc, UCB, Speakers bureau: AbbVie, Amgen, Celgene, Lilly, Janssen, Novartis, Pfizer Inc, UCB, Philip Helliwell: None declared, Oliver FitzGerald: None declared, Robin Waxman: None declared, Anna Antony: None declared, Laura C Coates: None declared, Deepak Jadon: None declared, Paul Creamer: None declared, Suzanne Lane: None declared, Marco Massarotti: None declared, Charlotte Cavill: None declared, Mel Brooke: None declared, Jonathan Packham: None declared, Eleanor Korendowych: None declared, Anya Lissina: None declared, Neil McHugh: None declared